The Catholic Church through the ages a history - Vidmar, John. (New York : Paulist Press, 2005)
"Renowned Catholic historian Christopher Dawson divided the history of the Catholic Church into six "ages" or 350- to 400-year periods that each began with great vitality and ended in decline and loss. In The Catholic Church Through the Ages Fr. John Vidmar surveys the history of the church, from its beginnings up to Pope Benedict XVI's pontificate, through Dawson's lens. He writes with enthusiasm and a down-to-earth quality born of years of teaching. Each chapter ends with an annotated list of readings and audio-visuals, and even includes historical novels to help convey a "feeling" for an age. Book jacket."--BOOK JACKET.
Introduction I. The First Age of the Church (33-330 AD) -- The Early Church -- A. Jewish Sources of Christianity -- B. Roman Sources of Christianity -- C. Influence of Jewish and Sources on Christianity -- D. Christian Sources -- E. Paul -- F. Attacks on Christianity -- G. Rival religions -- H. The Life of the Early Church -- I. The End of the First age -- J. Recommended Readings -- K. Notes -- II. The Second Age of the Church (330-650 AD) -- The Age of the Fathers -- A. The Fathers of the Church -- B. The Papacy -- C. The First Christological Councils -- D. St. Augustine (354-430) -- E. The Veneration of the Saints -- F. The Rise of Monasticism -- G. The End of the second age -- H. Recommended Reading -- I. Notes -- III. The Third Age of the Church (650-1000) -- The Dark Ages -- A. Islam -- B. The Byzantine Church and the Eastern Schism -- C. The Barbarians -- D. The Papacy (955-1057) -- E. The End of the Third Age -- F. Recommended readings -- G. Notes -- IV. The Fourth Age of the Church (1050-1450) -- The Middle Ages -- A. The Crusades -- B. The New Religious Orders -- C. Scholasticism -- D. Medieval Mysticism -- E. The Medieval Inquisition -- F. The Spanish Inquisition -- G. Innocent III -- H. The Decline of the Papacy -- I. The End of the Fourth Age -- J. Recommended readings -- K. Notes -- V. The Fifth Age of the Church (1450-1789) -- Protestant and Catholic Reformations -- A. The Renaissance -- B. The Reformation on the Continent -- C. The English Reformation -- D. The Reformation in Scotland -- E. Protestantism -- F. The Catholic response -- G. The Missions (1500-1800) -- H. The End of the Fifth age -- I. Chronology of the Reformation -- J. Recommended Readings -- K. Notes -- VI. The Sixth Age of the Church (1789-present) -- The Modern Age -- A. The Enlightenment or the Age of Reason -- B. The French Revolution -- C. The Aftermath of Revolution -- D. The Catholic Church in the United States -- E. Social Catholicism -- F. The Revival of the Missions (1800-2000) -- G. War and disctatorship -- H. Nazi Germany and the Catholic Church -- I. Post-World War II Catholicism -- J. The End of the Sixth age -- K. Recommended readings -- L. Notes -- Chronological list of the Popes.
Includes bibliographical references (p. 353-356) and index.
Description based on print version record.
Keywords: Catholic Church -- History; RELIGION / Christianity / Catholic; Electronic books